Informal structures as a factor of youth socialization: social and pedagogical aspect - Anastasiia Zakharchenko; Daniil Vavrenchuk; Yaroslava Shvedova (Scientific notes of the pedagogical department, 2023)
Informal youth structures are a diverse and non-transferable phenomenon in our modernity. A person joins an informal group to be satisﬁed, ask for respect, mutual assistance, mutual protection and close communication. The empirical base of the study is made up of data, subtracting the hour of the experiment, as it was carried out with the help of Google Form (141 persons, most of the interviews were conducted in 18 to 22 years). The main century group, as it took part in the internship, were young people from 13 to 23 years old, so that schoolchildren and students, could take a part in diﬀerent subcultures of fandoms. As a reminder of the research carried out, the result of the interaction of young people with informal structures / subcultures is both positively and negatively signiﬁed on the socialization of young people. In order to help the socialization of their developments, teachers can work indirectly through informal structures and secretly “control” those who are involved, promote the singing of values and reconciliation, and at the same time instill in and swing participants in these structures. Similar to the mutual understanding, search for sleepy ﬂoods, the exchange of knowledge can become a point in the interests and purposes of teachers and pupil, which promotes mutual understanding between them, as a result, accepting the eﬀectiveness of pedagogical practices.